2014
DOI: 10.2319/050714-330.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial force systems during bodily tooth movement with plastic aligners and composite attachments: A three-dimensional finite element analysis

Abstract: Objective: To describe, using a three-dimensional finite element (FE) model, the initial force system generated during bodily movement of upper canines with plastic aligners with and without composite attachments. Materials and Methods: A CAD model of an upper right canine, its alveolar bone and periodontal ligament, thermoformed plastic aligner, and two light-cured composite attachments were constructed. A FE model was used to analyze the effects of imposing a distal movement condition of 0.15 mm on the align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 16 publications
8
117
0
5
Order By: Relevance
“…According to Gomez et al, 5 teeth, attachments, and aligners were considered as isotropic and homogeneous materials. Teeth and attachments were considered as a unique body with rigid stiffness behavior.…”
Section: Materials Properties (Table 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…According to Gomez et al, 5 teeth, attachments, and aligners were considered as isotropic and homogeneous materials. Teeth and attachments were considered as a unique body with rigid stiffness behavior.…”
Section: Materials Properties (Table 1)mentioning
confidence: 99%
“…3,4 Forces originating from metal wire and bracket interactions are transmitted to tooth structures causing displacement; on the contrary, CAT outcomes are the result of a predetermined mismatch between tooth and aligner, which coincides with the desired position of the tooth. 3,5 The final dental position is reached by sequential aligners worn by patient 22 h/d, which progressively reposition the teeth by small amounts. 3,5,6 Additionally, several studies demonstrated that auxiliaries such as attachments and elastics are mandatory in CAT to achieve the predicted results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aligner, which corresponds to the new desired tooth position, is fitted on the dental arch, producing in each mismatch a force system that is directly transmitted to the tooth, generating the mechanical-biological chain of events that results in a new position of the tooth [15]. The interaction between the aligner and the tooth is complicated because of the complex and irregular shape of the aligner.…”
Section: Discussionmentioning
confidence: 99%
“…Gomez, et al [15] concluded that the plastic aligner system's biomechanical supplementary composite attachments generate the force system required to produce bodily tooth movement; the absence of biomechanical supplementary composite attachments can result in undesired inclination of the tooth during translation movements.…”
Section: Introductionmentioning
confidence: 99%